PENGARUH PRUDENCE TERHADAP ASIMETRI INFORMASI DENGAN KUALITAS LABA SEBAGAI VARIABEL MODERASI STUDI EMPIRIS PADA INDEXS LQ45 YANG TERDAFTAR DI BEI - Okti Fia Aristiani; Suharto Suharto; Gustin Padwa Sari (Akuisisi: Jurnal Akuntansi, 2017)
AbstractThe purpose of this research was to examine 1) the influence of prudence to the information asymmetry, 2) the effect of the earning quality as a moderating variable between prudence with information asymmetry. The research object was the ILQ45 company listed on the Indonesia Stock Exchange (BEI) for 3 years (2013-2015). Samples were 70 companies. The sampling technique used purposive sampling. Data were analyzed using SPSS 22.0 for Windows that consists of two types of analyze are multiple linier regression and analyze are Simple linier regression. Testing the hypothesis in this test using the t test, F test and coefficient of determination. Based on test result found that the prudence variable has no effect on information asymmetry. But prudence and moderating variables earning quality has effect towards the information asymmetry.Keywords: prudence, information asymmetry, earning quality, bid ask spread.